A METHODOLOGY TO IMPROVE SPEAKING SKILLS IN ENGLISH LANGUAGE LEARNING USING MOBILE APPLICATIONS - Akhmadova Feruza Zarifovna; Kholmurodova Dilnoza Kholmurodovna (Bright Mind Publishing, 2025)
The development of mobile applications as language learning tools has created new possibilities for enhancing English speaking competence. The current paper presents an analysis of the effectiveness of Facebook, HelloTalk, Tandem, and Duolingo in facilitating speaking skill acquisition by learners. Based on close observation of the app-specific features and how they support language practice, this article gives a guide for students and teachers to incorporate these tools in the development of speaking skills. The paper has benefits, weaknesses, and useful tips, and it points to the potential of these apps to create interactive learning opportunities.
Keywords: English speaking skills, mobile applications, language learning, interactive learning, Facebook, HelloTalk, Tandem, Duolingo.